Concrete Containing Palm Oil Fuel Ash (POFA) and Oil Palm Shell (OPS) Subjected to Elevated Temperatures - Jong, Lee Yee; Teo, DCL (Universiti Malaysia Sarawak (UNIMAS), 2015)
Nowadays, waste products such as Palm Oil Fuel Ash (POFA) and Oil Palm Shell (OPS) are produced in large quantities from the agriculture industry on a daily basis. Improper disposal of the agriculture wastes at landfills contributes to environmental pollution. The cost of construction material increases when the demand is high. Therefore, reutilization of these waste products not only reduces the cost of construction material but also minimizes waste disposal problem. In this research, waste POFA and OPS as cement and aggregate replacement respectively are used to produce a ‘greener’ concrete. This paper presents the effects of elevated temperatures on POFA OPS concrete. A concrete made from OPS aggregates (0% POFA) was also produced as a comparison. From the results obtained, it was observed that the formation of hair-line cracks on the surface of POFA OPS concrete specimen was less visible than OPS concrete specimen. All concrete specimens experience mass loss after being subjected to elevated temperatures. In terms of compressive strength, both OPS concrete and POFA OPS concrete specimen experienced a decrease in strength after being subjected to elevated temperatures. However, the POFA OPS concrete specimen showed better strength performance as compared to OPS concrete specimen at elevated temperatures of 200˚C to 500 ˚C.